2005
DOI: 10.1111/j.1532-5415.2005.53274.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Chronically Ill Seniors' Attitudes About Discussing Death and Postmortem Medical Procedures

Abstract: Proxy decisions about postmortem medical procedures must consider the dead patient's likely preferences. Ethnic- and sex-based attitudes surely underlie such preferences but lack sufficient characterization to guide decisions. Therefore, this exploratory study interviewed Mexican-American, Euroamerican, and African-American seniors in San Antonio, Texas, for their attitudes about discussing death before it occurs and about organ donation, autopsy, and practice on cadavers. A rigorous content analysis identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Research has shown that there may be significant cultural differences in the way individuals and families cope with dying and death. (43,44,45) Our study population was largely white (78%) which raises the question as to whether these results are generalizable to other populations. In addition, of eligible decedents for whom we had chart abstraction, our response rate with valid QODD responses was only 41.2%.…”
Section: Limitationsmentioning
confidence: 87%
“…Research has shown that there may be significant cultural differences in the way individuals and families cope with dying and death. (43,44,45) Our study population was largely white (78%) which raises the question as to whether these results are generalizable to other populations. In addition, of eligible decedents for whom we had chart abstraction, our response rate with valid QODD responses was only 41.2%.…”
Section: Limitationsmentioning
confidence: 87%
“…Our study did not include participants from two ethnic groups (Navajo Indians and Hmong individuals) in which there is a belief that discussing the possibility of death can cause harm to the patient (32,33). In general, because of the cultural variability in attitudes on discussing death, our findings should be applied only with great caution to these ethnic groups and others-including African Americansfor whom similar beliefs are common (34). We interviewed subjects at only one timepoint during a patient's ICU stay (between Days 3 and 5 of the patient receiving mechanical ventilation).…”
Section: Discussionmentioning
confidence: 99%
“…We explored beliefs about dying among Mexican Americans (MAs), Euro-Americans (EAs), and African Americans (AAs) [27][28][29][30] as well as their gender subgroups. We considered gender …”
Section: Methodsmentioning
confidence: 99%